Development characteristics of multi-scale fracture network systems in metamorphic buried hills - Mi, Lijun; Fan, Hongjun; Fan, Tingen; Gong, Lei; Niu, Tao; Su, Xiaocen; Luo, Jianghua; Sun, Yonghe (Frontiers in Earth Science, 2023)
Natural fractures are regarded as important reservoirs and effective seepage channels at metamorphic buried hills. Continuous networks associated with multi-scale fractures with good connectivity is critical for high-quality reservoirs as well as high and stable production in tight metamorphic rocks. The multi-scale fractures in Bozhong 19-6 metamorphic buried hills were well characterized through integrating imaging log, cores, thin-sections, and scanning electron microscope, etc. After that, power-law distribution of multi-scale fractures was established to understand contribution of fractures to reservoir quality and figure out structure models of fracture networks as well as their impact on production. Results show that parameters of fracture systems vary regularly with fracture scales. Fracture development, e.g., cumulative surface density, increases as a power law function with decreasing fracture size from macro to micro (e.g., opening and/or length), where storage space associated with micro fractures is also increased. Reversely, fracture connectivity and permeability follow a significant decreasing trend. Five structure models of fracture network were established based on combination pattern of multi-scale fractures: multiple fracture networks with multi-scale and high-density, multiple fracture networks with large-scale and mid-density, multiple fracture networks with small-scale and high-density, multiple fracture networks with large-scale and low-density, and single fracture network with small-scale and low-density. The former two can be widely developed into high-quality reservoirs, contributing greatly to high and stable yields. Fracturing is required for the third and the fourth to obtain stable production, while it is difficult for the fifth to obtain industrial oil and gas flow.